The Measurement of Operator Level Labor Productivity in PT. X Packaging - Sahat Dapottua Sitompul (Institute of Computer Science (IOCS), 2021)
The aim of the study is to find out the measurement of operator level labor productivity in X packaging workstation company. The problem of the study is Measurement of Workforce Productivity Level Operator Using the Work Sampling Method. The study of work measurement is intended to determine the standard / standard time of work and can provide good decisions in determining the optimal number of workers. the method use is qualitative descriptive data in the form of words, pictures, and not numbers. These data can be obtained from interviews, field notes, photos, videos, tapes, personal documentation, notes or memos, and other documentation. the result of the study are 1)The Average Earning Percentage for each worker 2)For worker 1 is 0.8978 for worker 2 is 0.8843 for workers 3 is 0.88453) The standard time required to complete one work cycle (completing one unit) is 0.188 hours4) The Number of Actual Workers = 3 people5) The number of Standard Workers based on the calculation results is 4 people.